Acoustic paramagnetic resonance spectra of Cr2+ in MgO and CaO - Shellard, Ian John (1978)
The Acoustic Paramagnetic Resonance (APR) of the chromous ion in two cubic host lattices, MgO and CaO, has been investigated for phonons of frequency around 9.5 GHz and temperatures in the range 1.51 K to 4.2 K. An iron-cored electromagnet produced magnetic fields continuously variable from 0 to 2 Tesla, the direction of magnetic field could be varied through 90 degree in the same plane as the phonon direction. Experiments were performed in which a variable uniaxial stress could be applied to a crystal of Cr2+ in MgO, giving information about the effects of local lattice strain on the APR spectrum. A change in the g-value of one resonance line with applied stress was observed, and, from this, the value of the strain coupling constant could be obtained. The experimental results enabled values for the parameters 3r (Jahn-Teller tunnelling splitting) and K (spin-orbit splitting) to be obtained, which were compared with those obtained by other methods. Further experiments were performed on Cr2+ in CaO in which the direction of the applied magnetic field could be changed by rotating the sample crystal about the phonon direction, enabling the field to be aligned with the crystal <111> direction. The theoretical prediction (Fletcher (1971)) that strain broadening of the resonance lines should be reduced under these conditions was demonstrated. Experiments were performed at two separate frequencies and two separate temperatures, and the results used as data for a computer programme which gave the values of the various parameters of the system, and thus allowed a low-lying energy level diagram to be predicted. There were similarities between this diagram and the accepted energy-level diagram of Cr2+ in MgO, as would be expected. The differences were attributed to die difference in the lattice constants of the host materials.